Danger in Paradise: A Tale of Salmonella. Issue 1 (January 2018) - Dobosz, Anna; Jagarlamudi, Rajasekhar; Ferguson, Eric; Otto, Michael; Kothari, Neelay
Abstract : Abstract: Salmonella -causing osteomyelitis of the sacroiliac joint in healthy young adults is extremely rare. We report a case of a young healthy woman who presented with fever and low back pain after a trip. She was subsequently found to have Salmonella oranienburg bacteremia and associated sacroiliac osteomyelitis. After prolonged parenteral and oral antibiotics, she recovered without complications. Abstract : Salmonella causing osteomyelitis of the sacroiliac joint in healthy young adults is extremely rare. The authors report a case of a young healthy woman who presented with fever and low back pain after a trip abroad. She was subsequently found to have Salmonella oranienburg bacteremia with associated sacroiliac osteomyelitis. After prolonged parenteral and oral antibiotic courses, she recovered without complications. Increased awareness and aggressive treatment may be needed for at-risk and infected patients.